Determination of antioxidant activity, total phenolic and total flavonoid content in Elaeis guineensis / Siti Nur Lisha Mohd Ghazali - Mohd Ghazali, Siti Nur Lisha (Faculty of Plantation and Agrotechnology, 2018)
Oil palm or Elaeis guineensis is one of the world 's valuable crops, from family Arecaceae. It has been cultivated in more than 20 countries, all of them tropical with warm, moist environment. Oil palm is a rich natural source of phenolic with flavonoid as the main constituents. These phenolics are potent antioxidant that can be used in food industry, cosmetics and others . Therefore, the study was aimed to determine the effect of three types of solvent and different plant parts toward Antioxidant Activity (AOA), Total Phenolic Content (TPC) and Total Flavonoid Content (TFC) to support further studies on these natural compound. Different types of solvent used for extraction and analyzation labelled as SI (Methanol), S2 (Ethyl acetate) , S3 (Hexane) . Crude extraction was done for further analysis of the compounds. Various plant parts were also used to determine the effect of different plant parts toward antioxidant, TPC and TFC which is PI (Leaves), P2 (Frond) , P3 (Fresh Fruit Bunch/FFB) and P4 (Empty Fruit Bunch/EFB). The antioxidant was analyzed using DPPH method , TPC by folin ciocalteu assay and TFC by aluminium chloride colorimetric assay. These samples were determined by using Ultraviolet (UV) spectrophotometer. The result from ANOVA indicate that there was significant difference (P < 0.05) in the extracting ability of each solvent and different plant parts for AOA, TPC and TFC. AOA also showed a negative correlation with TPC and TFC based on Pearson product moment correlation. Generally, the result suggest that methanol give the highest antioxidant activity, TPC and TFC compared to ethyl acetate and hexane. Therefore, solvent used should be select properly to allow for a high level of extraction efficiency.